Fusion‐activated cation entry (FACE) via P2X4 couples surfactant secretion and alveolar fluid transport. Issue 4 (10th January 2013) - Thompson, Kristin E.; Korbmacher, Jonas P.; Hecht, Elena; Hobi, Nina; Wittekindt, Oliver H.; Dietl, Paul; Kranz, Christine; Frick, Manfred
Abstract : Two fundamental mechanisms within alveoli are essential for lung function: regulated fluid transport and secretion of surfactant. Surfactant is secreted via exocytosis of lamellar bodies (LBs) in alveolar type II (ATII) cells. We recently reported that LB exocytosis results in fusion‐activated cation entry (FACE) via P2X4 receptors on LBs. We propose that FACE, in addition to facilitating surfactant secretion, modulates alveolar fluid transport. Correlative fluorescence and atomic force microscopy revealed that FACE‐dependent water influx correlated with individual fusion events in rat primary ATII cells. Moreover, ATII cell monolayers grown at air‐liquid interface exhibited increases in short‐circuit current ( I sc ) on stimulation with ATP or UTP. Both are potent agonists for LB exocytosis, but only ATP activates FACE. ATP, not UTP, elicited additional fusion‐dependent increases in I sc . Overexpressing dominant‐negative P2X4 abrogated this effect by 50%, whereas potentiating P2X4 lead to 80% increase in I sc . Finally, we monitored changes in alveolar surface liquid (ASL) on ATII monolayers by confocal microscopy. Only stimulation with ATP, not UTP, led to a significant, fusion‐dependent, 20% decrease in ASL, indicating apical‐to‐basolateral fluid transport across ATII monolayers. Our data support the first direct link between LB exocytosis, regulation of surfactant secretion, and transalveolar fluid resorption via FACE.—Thompson, K. E., Korbmacher, J. P., Hecht, E., Hobi, N., Wittekindt, O. H., Dietl, P., Kranz, C., Frick, M. Fusion‐activated cation entry (FACE) via P2X4 couples surfactant secretion and alveolar fluid transport FASEB J. 27, 1772–1783 (2013). www.fasebj.org